An experimental study of the moisture-induced degradation characteristics of GFRP-concrete interface - Jia-Xiang Liew; Peng Zhang; Ming-Feng Kai; Jian-Guo Dai (Materials & Design)
The durability of FRP-concrete interfaces is critical for the long-term performance of FRP −reinforced concrete structures. However, the degradation mechanisms of this interface, particularly in moist environments, remain poorly understood. This study employs novel experimental methods to investigate the effects of moisture at the Glass FRP (GFRP)-concrete interface by analysing relative humidity, micro-mechanics and chemical properties using capacitive humidity sensors, nano-indentation, FTIR spectroscopy, SEM and EDS. The results demonstrate varying degradation levels across the glass fibre, interphase region and resin matrix, with the interphase region exhibiting the most rapid degradation. FTIR analysis revealed significant resin matrix hydrolysis due to the substantial breakage of vinyl ester chains. SEM and EDS analysis verified the dissolution process of glass fibres, as evidenced by their pitted surface morphology. The dissolution was predominantly localized to the fibres at the GFRP bar’s surface, with the internal fibres maintaining their surface integrity. These findings provide critical insights into the moisture-induced degradation mechanisms at the GFRP-concrete interface, advancing the understanding of long-term durability in FRP-reinforced structures.